Current trends and prospects of tourism development in Germany - Balabanov, Gennadiy (Human Geography Journal, 2025)
Modern Germany is one of the leaders in the world and in Europe in terms of the scale and level of tourism development. The main reasons for this leadership in terms of the offer of tourist services include: the diversity of the natural environment, which contributes to the development of a wide range of recreational activities; unique in its wealth of historical and cultural resources; a developed network of various accommodation and catering establishments; the hospitality of the local population and a low level of crime; a dense network of transport and information and communication infrastructure; extensive experience in successfully organizing large-scale events, etc.Analysis of the problematic information field showed insufficient attention to a holistic, comprehensive disclosure of the dynamics and structure of the travel and tourism sector in Germany under the influence of external and internal development factors. The purpose of the study: to determine the features of the dynamics of development and structure of tourism in Germany in industry, functional and territorial aspects, to outline priorities for the future, to determine the role of German experience in the restoration and modernization of tourism in Ukraine. The most important external factor for the development of tourism in Germany in the period 2017-2024 was the COVID-19 pandemic. The long-term upward trend of the tourism industry under the influence of the pandemic changed in 2020 to a deep crisis. The number of overnight stays in tourist accommodation establishments in Germany in 2020 compared to 2019 decreased by 39%, residents' spending on travel abroad decreased by 59.2%, and Germany's income from foreign travelers decreased by 52%. Only thanks to the extraordinary efforts of the state and the private tourism business, this crisis was largely overcome in 2024.A hypothetical judgment is put forward that the direct impact of the Russian-Ukrainian war on tourist flows and spending in Germany is the growth of demand for recreational and tourist services within the country due to refugees from Ukraine. The author sees the main lever of influence on reducing the deficit of the balance of payments in Germany under the article "Travel" as the growth of inbound tourism. The current structural proportions between: 1) different types of tourism (domestic, inbound and outbound); 2) leading tourism industries (transport; accommodation; food and beverage; car rental and goods for sports and recreation; travel agencies, tour operators and other booking services); 3) tourist trips for various purposes (private or business); 4) tourism development in different regions and cities of the country. A trend towards strengthening the competitive positions of the 5 eastern states in the national market of tourist services has been identified. The share of the 5 new states in the total number of overnight stays in tourist accommodation establishments in Germany has been growing over the past 25 years: 2000 – 10.9%, 2010 – 16.8%, 2020 – 16.6%, 2024 – 17.2%. An important role in the process of structural analysis was played by the methods of hierarchical decomposition and rating assessment (ranking) of NUTS-1 and NUTS-2 regions.Using the rating assessment (ranking), the level of tourism development of the federal states of Germany was determined. The leaders of the rating are Bavaria, Baden-Württemberg, Lower Saxony and Schleswig-Holstein. Reliance on the method of hierarchical decomposition in relation to the spatial development of tourism in Germany involves a detailed analysis, a kind of “game of scale”, which is demonstrated by the example of Bavaria. A comparison of the ranked series of the states for 2019, 2020 and 2024 showed that the pandemic did not significantly affect the picture of the spatial development of tourism in Germany. This is likely due to the leading role of domestic tourism in the national arena compared to inbound tourism. The priorities of the German travel and tourism sector for the future have been and remain sustainable and inclusive development, technological innovation and digitalization, modernization of transport infrastructure and increasing competitiveness in the global market. The feasibility of using Germany's experience to restore and modernize tourism activities in Ukraine is emphasized.